The Hare Krishnas in Bali: Localized Religion and New Religious Movement - Ravinjay Kuckreja (Religio: Jurnal Studi Agama-agama, 2022)
As the Balinese sought official religious acceptance in Indonesia, they formalized their ethnic customs and transformed them into a universal religion with an Abrahamic model called “Agama Hindu Dharma”. In aligning itself with Hinduism, the Balinese had to restructure their internalized indigenous faith and share it with Hindus beyond the island, including with others in the archipelago and the religious hearth of India. The International Society for Krishna Consciousness (ISKCON), commonly known as The Hare Krishna Movement, is a Hindu-based New Religious Movement. With their active presence in Bali, they provided an informative and devotional perspective for inquisitive Hindus. Preferring their local expression of Hinduism instead, ISKCON books and teachings were banned in 1984 for disrupting public order during the repressive era of President Suharto. The political reformation of 1998 allowed for the recognition of ISKCON, but the exclusivism of Hare Krishna members threatened many orthodox Balinese Hindus. This opposition culminated in 2020, resulting in a decree restricting all non-Balinese Hindu sects from practicing in the Hindu-majority province. This paper documents the formalization of the indigenous Balinese theology and its recent interaction with a multinational New Religious Movement.